Essays on political economy, leader demographics and corporate finance: evidence from China - Chu, Honghu (2021)
Recent trends suggest that political considerations in corporate financial decision-making have become of increasing interest to financial studies researchers. Firms make financial decisions in response to a given institutional setting (North, 1992; La Porta, 1997; and Aghion, 2004) and realise the importance of the trade-off between the delegation of power to leaders and the need to control them to avoid tyranny. China is an emerging market, and with a dramatic development over a short span of 40 years, she has stood firm as the world’s number two economic power. With the enormous size of the economy, which provides rich sources of information, and with her unique political-institutional settings, which leads to the coexistence of state-owned sectors and private sectors, our study of political factors of corporate governance, more specifically, the impact of political connections of business leaders on firm financial decision making and performance in the Chinese financial markets provides compelling new evidence which can inform the development of corporate governance theories, since leaders’ political connections and demographics have been an important focus and frontier in this area.